2020
DOI: 10.1093/bib/bbaa317
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the immune infiltrate modulation in cancer and response to immunotherapy by MIXTURE—an enhanced deconvolution method

Abstract: The accurate quantification of tumor-infiltrating immune cells turns crucial to uncover their role in tumor immune escape, to determine patient prognosis and to predict response to immune checkpoint blockade. Current state-of-the-art methods that quantify immune cells from tumor biopsies using gene expression data apply computational deconvolution methods that present multicollinearity and estimation errors resulting in the overestimation or underestimation of the diversity of infiltrating immune cells and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The large number of primary tumor transcriptional profiles across disease subtypes available from TCGA provides a unique cohort to estimate the impact of age on tumor immune cell composition. We apply the MIXTURE immune-cell-type deconvolution algorithm ( Fernández et al, 2021 ) to infer the absolute proportions of immune cell types from RNA-seq data derived from pan-cancer TCGA samples. The algorithm provides an absolute proportion that describes the portion of total immune content that a particular immune cell type makes up in a sample but is normalized to be comparable across all samples in the dataset by multiplying the inferred relative proportion by a scaling factor that measures the total immune content in the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large number of primary tumor transcriptional profiles across disease subtypes available from TCGA provides a unique cohort to estimate the impact of age on tumor immune cell composition. We apply the MIXTURE immune-cell-type deconvolution algorithm ( Fernández et al, 2021 ) to infer the absolute proportions of immune cell types from RNA-seq data derived from pan-cancer TCGA samples. The algorithm provides an absolute proportion that describes the portion of total immune content that a particular immune cell type makes up in a sample but is normalized to be comparable across all samples in the dataset by multiplying the inferred relative proportion by a scaling factor that measures the total immune content in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Immune Cell Type Deconvolution from Bulk RNA-Sequencing Data The MIXTURE algorithm (Ferná ndez et al, 2021) builds on the nu-Support Vector Regression framework used by CIBER-SORT (Newman et al, 2015) for particular use with noisy tumor samples. MIXTURE applies Recursive Feature Selection to make the cell type deconvolution more robust to noise and collinearity, and was thus designed to improve performance on tumor data.…”
Section: Differential Methylation Analysis With Agementioning
confidence: 99%
“…Accumulating data have shown that immune cells for tumor infiltration in the tumor microenvironment play an important role in tumor development 34 , 35 . However, it remains unclear how CCGs influence immune cell infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…In total, we review 39 reference-based methods (MuSiC ( 79 ), DWLS ( 80 ), AdRoit ( 112 ), spatialDWLS ( 113 ), Scaden ( 81 ), LinDeconSeq ( 109 ), DigitalDLSorter ( 82 ), AutoGeneS ( 114 ), RNA-Sieve ( 83 ), DecOT ( 111 ), BayICE ( 94 ), DeconPeaker ( 73 ), SCDC ( 84 ), DAISM-DNN ( 115 ), CPM ( 85 ), MOMF ( 86 ), BisqueRef ( 116 ), deconvSeq ( 101 ), DeCompress ( 87 ), DeMixT ( 117 ), CIBERSORT ( 107 , 108 ), MethylResolver ( 104 ), MIXTURE ( 105 ), FARDEEP ( 118 ), NITUMID ( 110 ), MySort ( 119 ), PREDE ( 57 ), quanTIseq ( 106 ), DeconRNASeq ( 120 ), DCQ ( 88 ), dtangle ( 102 ), DESeq2’s unmix ( 121 ), ARIC ( 100 ), EMeth ( 122 ), ImmuCellAI ( 89 ), EPIC ( 103 ), TICPE ( 90 ), BayesPrism ( 98 ), Bseq-SC ( 99 )), 10 reference-free approaches (Linseed ( 123 ), TOAST ( 91 , 92 ), debCAM ( 124 ), CellDistinguisher ( 125 ), deconf ( 126 ), BayCount ( 127 ), BayesCCE ( 74 ), ReFACTor ( 93 ), DeconICA ( 128 ), SMC ( 97 )) and 4 semi-reference-free techniques (Deblender ( 95 ), MCP-counter ( 129 ), BisqueMarker ( 116 ), DSA ( 96 )).…”
Section: Technical Description Of Deconvolution Methodsmentioning
confidence: 99%